The effects of treating the seedlings of a Strawberry (L. Fragaria Ananassa) plant with a Colchicine on the Characteristics of its productivity - Mahmoud, Youssef Abdel Rahman; Obeid, Iyad Assi; Ali, Nizar Asleman (Journal of agricultural, environmental and veterinary sciences, 2019)
An experiment was conducted in the research station Horticulture and landscape gardening Dept./college of Agriculture university of Diyala for the period from 2016/12/15 up to 2017/7/1. to study the effect of colchicine and its effect on the properties of the chemical properties of the fruit of the plant, because most of the species in the country with low productivity, of the Strawberry plant when treating its apical part by the Colchicine with concentrations of zero, 0.05, and 0.1%. The number of treatment times was (one treatment and two treatments). The results of the showed that the plants that treated with 0.1% Colchicine were Increased the number of fruits (11.650 fruit/plant), the size of fruit (3.033 cm3), the weight of a single fruit (9.683 mg), the amount of productivity in the plant (108.233 g/plant), the percentage of acidity (0.707%), the amount of vitamin C (46.969 mg/100g),. when Compared with the control value of treatment, it found that the control value of treatment has more number of stomata with average (26 stomata.mm2). while with the treatment of 0.05% concentration, the percentage of the sugars was the highest around (16.488%). The treatment of the top of the plant did not affect the number of fruits per plant, while the size of the fruit affected the date of treatment exceeded the plants treated twice the plants on the treatment of one time at a rate of 8.388 cm 3. As for the fruit weight and the quantity of plant yield, there was no significant difference between the date of treatment of the plant. Also, there was no effect of the date of treatment in the percentage of total acidity of the fruit. The effect of the double interaction between both the concentration and the treatment date. The results indicate that the highest number of fruits per plant, the quantity of fruit per plant and the quantity of vitamin C in fruit is achieved when treated with 0.1% The fruit weight and the total percentage of total sugars eliminated all the interference coefficients on the comparison treatment. The results also indicate that the highest rate of fruit size and the percentage of total acidity was in the treatment 0.1% and two treatment (9.910 cm 3) and (0.755%) respectively.
Keywords: Strawberry; Colchicine; apical plant; Characteristics